Analysis of consumer behaviour to the price factor on the footwear market for runners - Burillo, P.; Pérez González, B. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2016)
In Spain 2,274,074 million pairs of shoes were sold to runners (about 175 million of euros). The economic sector of sports equipment for runners may be living its best moment except for as outrageous war of brands and prices that some authors describe. This study examines perceptions of consumers regarding the footwear market for runners. It was designed and validated a questionnaire to 274 runners (10 km, half marathon or marathon). The technical variables such as comfort, lightness, cushioning and durability are more appreciated than price. Only the aesthetic has a lower score. The price is not the most important factor in the purchase decision. Men prefer a better price than technical and aesthetic features as well as the most experienced and long distance runners.